The Use of the Figma Design Application with the ATM (Amati, Tiru, Modifikasi) Method in Class X Students at SMK Negeri 3 Medan - Sitohang, Norenta (Literacy: Journal of Education and Social Science, 2025)
This study aims to examine the effectiveness of the use of the Figma design application with the ATM (Observe, Imitate, Modify) method in improving the design skills and creativity of grade X students at SMK Negeri 3 Medan. The research method used is qualitative descriptive with participatory observation techniques, interviews, documentation, and analysis of students' work. The research was conducted on 30 students majoring in Software Engineering through educational field practice. The results show that the ATM approach is able to improve the understanding of design principles, technical skills in the use of Figma, as well as encourage innovation in design modification. Digital collaboration also helps develop communication and teamwork skills. Although there were initial obstacles in adapting Figma's features, they could be overcome through intensive mentoring. Thus, the integration of Figma and the ATM method has proven to be effective as a design learning strategy that is applicable, creative, and in accordance with industry needs.